Before the Mughals: Material Culture of Sultanate North India - Flood, Finbarr Barry (Muqarnas, 2019)
This article presents an overview of the current state of knowledge regarding the material culture of north India under the Delhi sultans and the regional sultanates that emerged in Bengal, Gujarat, Jaunpur, and Malwa during the fourteenth and fifteenth centuries. Highlighting lacunae in existing scholarship, it also draws attention to material and textual sources that underline the strong transregional filiations of Sultanate art and architecture. It suggests that negotiations between regional artistic forms and styles and those that reflect transregional connections in Sultanate art and architecture anticipate a feature often seen as characteristic of early Mughal art and architecture.